Investigation of shear slip in hot fractured rock. (August 2019) - Huang, Kai; Cheng, Qinglu; Ghassemi, Ahmad; Bauer, Stephen
Abstract: This paper presents the results of a shear slip experiment in hot rock and its simulation and analysis using 3D coupled thermo-poromechanical model with the aim of assessing the role of pore pressure and temperature change on shear slip in granitic rock. The test is carried out in a triaxial system at representative reservoir pressure and temperature using right circular cylindrical specimens of Westerly granite with a 30° precut and ground surface. After the pore pressure and temperature were stabilized, the differential stress and absolute pore pressure were systematically varied to produce different effective stress states to evaluate the shearing response of the saw-cut fracture. The key objective of the experiment is to test the cooling effect on the fracture slip. The experimental results were then analyzed using a newly developed 3D thermo-poromechanical finite element model which uses traditional 4 node tetrahedron elements for intact rock deformation and transport processes. Zero thickness contact interface element is employed to capture the closure and slip on the fracture surface. The stick/slip state of fracture is determined by the Mohr-Coulomb criterion. Simulation results show that the convective cooling effects on rock/fracture surface promote deformation and slip of the fracture. The cold fluid cools the surrounding rock material and results in normal stress reduction that causes portions of the fracture surface to undergo stick/slip state changes, and induces irreversible slip. The experimental work along with modeling provides a physics-based understanding of the role of coupled processes on shear stimulation phenomenon.